2004
DOI: 10.1093/cercor/bhh037
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Functional Cortical Topographies for Working Memory Maintenance of Voice Identity and Location

Abstract: In order to ascertain whether the neural system for auditory working memory exhibits a functional dissociation for spatial and nonspatial information, we used functional magnetic resonance imaging and a single set of auditory stimuli to study working memory for the location and identity of human voices. The subjects performed a delayed recognition task for human voices and voice locations and an auditory sensorimotor control task. Several temporal, parietal, and frontal areas were activated by both memory task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 36 publications
6
37
0
Order By: Relevance
“…Furthermore, recordings in monkeys performing spatial delayed response tasks have shown that the DLPFC contains neurons activated by auditory or visual spatial cues (KikuchiYorioka & Sawaguchi, 2000). Evidence for a DLPFC auditory spatial-processing domain has also been shown in human imaging studies (Bushara et al, 1999;Rama et al, 2004). In one study, maintenance of spatial and nonspatial information preferentially activated dorsal and ventral prefrontal regions, respectively (Rama et al, 2004).…”
Section: Evidence From Other Modalitiesmentioning
confidence: 74%
“…Furthermore, recordings in monkeys performing spatial delayed response tasks have shown that the DLPFC contains neurons activated by auditory or visual spatial cues (KikuchiYorioka & Sawaguchi, 2000). Evidence for a DLPFC auditory spatial-processing domain has also been shown in human imaging studies (Bushara et al, 1999;Rama et al, 2004). In one study, maintenance of spatial and nonspatial information preferentially activated dorsal and ventral prefrontal regions, respectively (Rama et al, 2004).…”
Section: Evidence From Other Modalitiesmentioning
confidence: 74%
“…In contrast to the studies reviewed in the previous paragraph, there have also been several reports demonstrating PFC working memory-related activity that is largely, but not entirely, overlapping for different stimulus domains (Gruber & von Cramon, 2003;Manoach et al, 2004;Rama et al, 2004;Rama, Sala, Gillen, Pek, & Courtney, 2001;Sala et al, 2003). Courtney and colleagues have interpreted these results as suggesting an organizational scheme of graded degrees of segregation and overlap of working memory storage functions of the PFC (e.g., Courtney, 2004).…”
Section: Human Neuroimagingmentioning
confidence: 91%
“…Evidence from both monkeys and humans had already suggested that there were multisynaptic corticocortical pathways in audition paralleling those in vision (Bruce et al, 1981;Wang et al, 1995;Andersen, 1997;Romanski et al, 1999;Rauschecker and Tian, 2000;Clarke et al, 2002;Kaiser et al, 2003;Rama et al, 2004;For review see, Shroeder and Fox, 2005). The metabolic mapping study not only lends strong support to that notion, but also allows simultaneous visualization of the territory occupied by all three of these proposed pathways.…”
Section: Comparison Of Auditory and Visual Mapsmentioning
confidence: 99%